Relation between Nucleic Acid Indices and Growth Rate in Fed and Fasting Juvenile Scup. (14th October 2013) - Mercaldo‐Allen, Renee; Kuropat, Catherine A.; Perry, Dean M.; Redman, Dylan H.
Abstract: The relationship between nucleic acid indices and daily instantaneous growth rate was determined for juvenile Scup Stenotomus chrysops in the laboratory. Weight‐based growth of Scup was measured for three 1‐week intervals during a 6‐week feeding experiment and showed a significant positive correlation with both RNA concentration (RNA; μg/mg tissue wet weight) and DNA concentration (DNA; μg/mg tissue wet weight), while the RNA: DNA ratio was not significantly correlated with the weight‐ or length‐based growth rate. The concentration of DNA showed a significant negative correlation with length‐based growth rate. Mean fish weight increased from 1.022 to 10.404 g, and mean TL increased from 43.219 to 85.377 mm. Changes in nucleic acid indices were measured in fish that were deprived of food over a 9‐d period. The RNA and RNA: DNA ratio values declined significantly within 5 d after fasting began, while DNA remained relatively stable. This study provides baseline nucleic acid values for fed and starved juvenile Scup over a range of fish sizes.